Konsep Politik Hukum Pengembangan Sumber Daya Manusia Transportasi Udara Nasional dalam Menghadapi Masyarakat Ekonomi ASEAN - Endang Puji Lestari (WARTA ARDHIA, 2015)
Legal policy in developing and providing air transportation’s human resources is the sub system of national transportation policy. There are two problems in this research, first, how is the regulation of Indonesia’s legal policy in air transportation’s human resources development? Second, how is the concept of legal policy of Indonesia’s air transportation human resources development? Regulation scope in providing and developing of air transportation human resources development consists of manpower planning, education and training, working opportunity and surveillance, monitoring as well as evaluation. Legal policy of regulation in providing and developing human resources that is conducted through delegated legislation requires sustainable policy such as the enactment of three Minister Regulations, namely the Minister of Transportation Regulation on The Development and Providing of Air Transportation Human Resources, the Minister of Transportation Regulation on The Implementation of Air Transportation Education and Training, and the Minister of Transportation Regulation on certificate of competency and license as well as arrangement of training program. The writer suggests the Ministry of Transportation to ratify immediately the three of the Minister of Transportation Regulations that have a basic delegated legislation as an answer to face ASEAN open sky policy. Keywords: legal policy, human resources, delegated legislation. Politik hukum pengembangan dan penyediaan SDM penerbangan merupakan sub-sistem dari kebijakan transpotasi nasional. Terdapat dua permasalahan dalam tulisan ini, pertama, bagaimana kebijakan politik hukum nasional Indonesia dalam pengembangan SDM transportasi udara nasional? kedua, bagaimana konsep kebijakan hukum pengembangan SDM transportasi udara nasional? Ruang lingkup pengaturan penyediaan dan pengembangan SDM penerbangan meliputi perencanaan sumber daya manusia (manpower planning), pendidikan dan pelatihan, perluasan kesempatan kerja, serta pengawasan, pemantauan, dan evaluasi. Politik legislasi pengaturan pengembangan dan penyediaan SDM yang dilakukan melalui delegated legislation di atas memerlukan kebijakan lanjutan berupa diundangkannya tiga peraturan menteri yaitu peraturan menteri perhubungan tentang penyediaan dan pengembangan sumber daya manusia di bidang penerbangan, peraturan menteri perhubungan tentang penyelenggaraan pendidikan dan pelatihan di bidang penerbangan, dan peraturan menteri perhubungan tentang sertifikat kompetensi dan lisensi serta penyusunan program pelatihan. Penulis menyarankan kepada Kementerian Perhubungan RI untuk segera mengundangkan ketiga peraturan menteri perhubungan yang telah memiliki dasar delegated legislation sebagai jawaban untuk menghadapi ASEAN open sky policy. Kata kunci: politik hukum, sumber daya manusia, delegated legislation.